Starches Modified by Combination of Phosphorylation and High-Voltage Electrical Discharge (HVED) Treatment - Ivanka Grgić; Marijana Grec; Artur Gryszkin; Tomasz Zięba; Mirela Kopjar; Đurđica Ačkar; Antun Jozinović; Borislav Miličević; Sandra Zavadlav; Jurislav Babić (Polish Journal of Food and Nutrition Sciences)
Starch is extensively used in the food industry as a texture modifier, a fat substitute, and in other applications. To optimise starch functional properties for specific use, it is subjected to various modifications. High-voltage electrical discharge (HVED) treatment, as a non-thermal and rapid process, was applied in this research as a single method and in combination with phosphorylation in order to explore its potential for improving starch physicochemical properties. Maize, wheat, potato, and tapioca starches were modified, and Na5P3O10 and Na2HPO4 were used for phosphorylation. Starch gelatinisation parameters (by DSC); paste clarity; and contents of amylose, damaged starch, and resistant starch were determined; and FTIR-ATR spectra were recorded. All modifications reduced the enthalpy of gelatinisation and decreased contents of amylose, resistant starch, and damaged starch. The effect of the HVED treatment on starch properties depended on starch type and combinations with chemicals. HVED could act as an aid in the starch phosphorylation process since the properties analysed were more effectively improved when HVED was combined with phosphorylation than by phosphorylation alone.